My first mister - Baum, Carol; Goldenring, Jane; Franklyn, Jill; Lahti, Christine 1950-; Total Film Group (Hollywood, California Paramount Pictures, 2001)
Jennifer is a 17-year-old Goth with multiple face-piercings and a fondness for graveyards. Randall is a middle-aged salesman with an obsessively tidy life and a fear of anything new. When these two opposites collide, the chain reaction sparks a life-altering meltdown for them both in this wickedly perceptive, critically acclaimed comedy. Desperate to escape the world of her infuriatingly cheery mother and mindless bimbo classmates, punk-rebel Jennifer impulsively applies for a job at Randall's decidedly conservative clothing store. Soon, to their mutual shock and surprise, an unlikely friendship blooms. But even as Randall attempts to show Jennifer the possibilities of her own future, Jennifer discovers the extraordinary secret haunting Randall's past. A wry, hilarious, powerfully emotional story of reaching out, making contact, and coping with the consequences.
Executive producers, Frank Hubner and Gerlad Green ; Co-executive producer, Jon F. Vein ; Director of photography, Jeffrey Jur ; Editor, Wendy Greene Bricmont.
Albert Brooks, Leelee Sobieski, Desmond Harrington, Carol Kane, Mary Kay Place, Michael McKean.
DVD (Region 1, NTSC) ; Dolby Digital
In English.
Keywords: Comedy -- Drama